2018
DOI: 10.3390/e20010047
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Complexity of Heart Rate Variability with Exercise Training Measured by Multiscale Entropy-Based Measurements

Abstract: Quantifying complexity from heart rate variability (HRV) series is a challenging task, and multiscale entropy (MSE), along with its variants, has been demonstrated to be one of the most robust approaches to achieve this goal. Although physical training is known to be beneficial, there is little information about the long-term complexity changes induced by the physical conditioning. The present study aimed to quantify the changes in physiological complexity elicited by physical training through multiscale entro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…The causal, directed interactions between brain regions at rest (brain-brain networks) and between resting-state brain activity and the ANS outflow (brain-heart links) have been studied by Duggento et al ( 120 ) showing that the amygdala, hypothalamus, brainstem and, among others, medial, middle and superior frontal gyri, superior temporal pole, paracentral lobule and cerebellar regions are involved in modulating the CAN. Previous studies reported that CI s is probably linked to the vagal control of HRV, while CI l seems to be more related (although not exclusively) to the sympathetic control of HRV ( 41 , 78 , 121 , 122 ).…”
Section: Discussionmentioning
confidence: 89%
“…The causal, directed interactions between brain regions at rest (brain-brain networks) and between resting-state brain activity and the ANS outflow (brain-heart links) have been studied by Duggento et al ( 120 ) showing that the amygdala, hypothalamus, brainstem and, among others, medial, middle and superior frontal gyri, superior temporal pole, paracentral lobule and cerebellar regions are involved in modulating the CAN. Previous studies reported that CI s is probably linked to the vagal control of HRV, while CI l seems to be more related (although not exclusively) to the sympathetic control of HRV ( 41 , 78 , 121 , 122 ).…”
Section: Discussionmentioning
confidence: 89%
“…The living organism can be considered a complex system and, as such, it is difficult to disentangle the influences caused by each mechanism, once their functions are highly interdependent [ 90 ]. This is the reason why many nonlinear HRV parameters are considered as “complexity measures”, in the sense that, although they are not clearly associated with specific physiological meanings, they are able to represent the general complexity of the system, attested by their important role as risk factors, prognosis and fitness [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…When myocardial electrical resistance and autonomic nervous balance remain unchanged, the complexity of heart rate dynamics is due primarily to the sufficiency of myocardial metabolism demand relative to oxygen and nutrient supply. This can explain why physical training increases the complexity of HRV 61 and why the resting energy expenditure displays significantly positive correlations with heart rate dynamics 62 .…”
Section: Remark For (1-1)mentioning
confidence: 98%